Analisis Daya Tarik Wisata Air Melalui Pendekatan Supply Demand: Studi Di Sendang Bulus Bungkal Ponorogo - Putri, Dela Tiara Putri; Aulia Mutakhidatul Umah; Dika Alvira Andaresta (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2023)
In the Ponorogo area, Sendang Bulus is one of the most well-known water attractions. As part of conservation efforts, Sendang Bulus was first applied to turtle cattle (Amyda cartilaginea). The existence of Sendang Bulus water tourism can be a contribution to the preservation of turtles as well as a tourist attraction that can be used for various activities, such as turtle observation, fishing, ecotourism education, cultural tourism, and photography. By using supply and demand strategies, this study aims to determine the attractiveness of Sendang Bulus water tourism in Pager Village, Bungkal, Ponorogo Regency. Supply analysis is based on the results of questionnaires and observations of resources that have the potential to become tourist attractions, while demand analysis is carried out by examining the results of literature studies and visitor perceptions through social media. The results of the study revealed that there was a discrepancy between supply and demand for several tourist attractions and supporting facilities/infrastructure at Sendang Bulus, caused by the relatively small number of turtles, the poor condition of the roads leading to tourist attractions, and poorly maintained game rides.